Shared parental responsibility: Stability of arrangements among separated Australian Families of young Children across two years - Losoncz, I (My University, 2008)
Recent reforms to the family law and Child Support Scheme systems in Australia emphasise the importance of shared parental responsibility after separation and the best interests of the child, and stress the key themes of: joint financial responsibility; substantial child contact with each parent where possible; shared decision-making by parents; and, assistance to reduce conflict and improve communication between separated parents. This article investigates each of these key themes, comparing data from Waves 1 and 2 of Growing Up In Australia: The Longitudinal Study of Australian Children (LSAC), concerning child support compliance, parent-child contact, shared decision-making, and parental conflict. The findings highlight the importance of post-separation working relationships between parents.
Keywords: Relationships; Relationships -- Separation; Families; Families -- Parents and Parenting; Families and relationships; Families; Relationships; Parents and Parenting; Separation; Families and relationships